Lower limbs micro-loading acutely attenuates repeated change-of-direction performance in male youth during small-sided soccer games - Mohamed Amine Ltifi; Hassane Zouhal; Ismail Laher; Ayoub Saeidi; Karuppasamy Govindasamy; Urs Granacher; Ridha Aouadi; Abderraouf Ben Abderrahman (BMC, 2023)
Abstract Background Soccer players often wear light-weighted wearable resistance (WR) attached to different body parts during the warm-up period with the aim to improve measures of physical fitness. However, the effect of WR on physical performance is unknown. This study evaluated the effects of WR with different micro-loadings on repeated change-of-direction (RCoD) performance while executing small-sided soccer games (SSG). Methods Twenty male soccer players aged 16.0 ± 1.5 years (body mass 74.0 ± 7.4 kg, body-height 175.0 ± 10.0 cm) volunteered to participate in this study. Following a within-subject study design, players performed four specific warm-up protocols in randomized order with a rest of 72 h between protocols: (1) WR micro-loadings with 0.1% of body mass (WR0.1); (2) WR micro-loadings with 0.2% of body mass (WR0.2); (3) WR micro-loadings with 0.3% of body mass (WR0.3); (4) no WR (control = CONT). After the warm-up protocols, players performed 2 sets of 20-min SSG. The RCoD was collected at the 8th min of SSG (SSG 1-8 min), the 15th min of SSG1 (SSG1-15 min), and at the 15th min of SSG2 (SSG2-15 min). Outcomes included mean and total RCoD indices (i.e., mean time and total time for each condition). Results Based on the outcomes of a two-way repeated measures analysis of variance (ANOVA), WR0.1 and WR0.2 were more effective than control in dampening the decrease of RCoD's total time during SSG1-8 min, and SSG2-15 min (small ES: 0.24-0.35; p < 0.05). However, no significant differences were observed between WR0.3 and control. In addition, WR0.1 and WR0.2 significantly affected the decreases in RCoD's mean best time during SSG1 and SSG2 which was observed in the unloaded condition (CONT) and consequently displayed a lower rate of RCoD performance decrease. Conclusion This study reports that wearing lower extremity WRs with micro-loads of 0.1% or 0.2% of body mass attenuates physical fatigue indicated in attenuated RCoD performance while executing SSG.